Expanding the boundaries of brand communities: the case of Fairtrade Towns. (31st January 2018) - Samuel, Anthony; Peattie, Ken; Doherty, Bob
Abstract : Purpose: This paper aims to further the authors' understanding of brand communities, and their role in brand co-creation, through empirical and theoretical contributions derived from researching the marketing dynamics operating within a successful but atypical form of brand community, Fairtrade Towns (FTT). Design/methodology/approach: The paper reflects a pragmatic application of Grounded Theory, which captured qualitative data from key "insiders", with a particular emphasis on FTT steering group members and their role as "prosumers". Data were gathered via ethnographic involvement within one town and semi-structured interviews with participants in others. Findings: FTTs, as brand communities, demonstrate elements of co-creation that go beyond the dominant theories and models within the marketing literature. They operate in, and relate to, real places rather than the online environments that dominate the literature on this subject. Unusually, the interactions between brand marketers and consumers are not the primary source of co-creation in FTTs. Instead, factors usually identified as merely secondary providers of additional brand knowledge become key initiators and sources of co-creation and active "citizen marketer" engagement. Originality/value: This study demonstrates how brand co-creation can operate in physical geographical communities in ways that are formal without being managed by conventional brand managers. It conceptualises FTTs as a nested and "glocalised" brand and demonstrates how steering group members facilitate the process of co-creation as prosumers. It empirically demonstrates how FTTs have evolved to become unusually complex brand communities in terms of the variety of stakeholders and the multiplicity of brands involved, and the governance of the localised brand co-creation process.